Effect of Current Ratio, Debt To Equity Ratio, Inventory Turnover and Capital Structure on Profitability: Pengaruh Current Ratio, Debt To Equity Ratio, Inventory Turnover dan Struktur Modal Terhadap Profitabilitas - Desy Fithry Aryanti; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2021)
The rapid need for telecommunications today is the demand for companies to be able to be innovative in their competition to generate maximum profits, in this research the aim is to find out whether profitability can be influenced by the Current Ratio, Debt To Equity Ratio, Inventory Turnover and Capital Structure in the IDX telecommunications company sector. From 2013 to 2019. The population was taken from the telecommunications sector on the IDX during 2013-2019. The overall sample of telecommunications companies on the IDX was 5 companies, so that the total financial statements observed were 35 financial statements for a period of 7 years. The method used is quantitative using the SPSS V 25 application, with a set of test tools used to test the predetermined hypothesis. In testing the hypothesis, the first revealed that profitability can be influenced by Current ratio, secondly profitability can be influenced by Debt to equity ratio, thirdly profitability cannot be influenced by Inventory Turnover, fourthly profitability cannot be influenced by Capital Structure.